Preparation method of phenolic hydroxyl-rich lignin derivative polyurethane flame-retardant foam material
The DOPO functional chain segment was introduced through lignin demethylation and Mannich reaction, and the reactive lignin flame retardant was prepared, and the condensation reaction with 4,4-MDI was carried out to form a phenolic hydroxylignin derivative polyurethane foam material, which was solved The problems of low refractory performance of polyurethane foam materials and relying on fossil resources for production have achieved efficient flame retardant and thermal barrier properties, and the materials are cost-effective.
Patent Information
- Application Number
- CN202411439592.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing polyurethane foam materials have low refractory properties and rely on fossil resources for the production process, which lacks sustainable preparation methods.
The DOPO functional chain segment was introduced through lignin demethylation and Mannich reaction, and a reactive lignin flame retardant was prepared and condensation with 4,4-MDI to form a phenolic hydroxylignin derivative polyurethane foam material.
The flame retardant and thermal barrier properties of polyurethane foam are significantly improved, the limit oxygen index value reaches 34.5%, reaching the V-0 level of UL94 flammability test, and the material is cost-effective, suitable for production from renewable biomass.
Smart Images

Figure CN119431733A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane foam materials, and in particular to a method for preparing a polyurethane flame-retardant foam material rich in phenolic hydroxyl lignin derivatives. Background Art
[0002] Polyurethane (PU) is a polymer synthesized by a condensation reaction between polyols (-OH) and isocyanates (-NCO). Due to its excellent thermal insulation properties, light weight, and durability, polyurethane foam is very suitable for use as a thermal insulation material in buildings. Since polyurethane is widely used and has low fire resistance, it is crucial to improve the fire resistance of polyurethane. In addition, since the polyols used in polyurethane production are heavily dependent on fossil resources, exploring sustainable methods to prepare renewable and eco-friendly polyurethane composites is crucial to the development of sustainable polyurethane.
[0003] As petroleum resources are depleted, renewable resources will become the main basis for the production of materials and chemicals. Among them, lignin has become one of the most abundant resources due to its low production cost. Lignin is the second largest natural polymer after cellulose and has a three-dimensional network structure composed of phenylpropane chemical units. Lignin has a phenolic structure and can be cross-linked with other chemicals to prepare composite materials with sustainable development potential, and lignin derivatives can provide high added value of flame retardant properties to composite materials. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a polyurethane flame retardant foam material of a phenolic hydroxyl-rich lignin derivative, wherein the polymer of the hydroxyl-rich lignin is modified by amination as a reactant, the lignin is demethylated by a molten salt hydrate system, and the functional chain segment of 6-(1-(4-aminophenyl)-1-(p-tolyl)ethyl)dibenzo[c,e][1,2]phosphine oxide 6-oxide (2NH2DOPO) is introduced into the lignin molecular structure through the Mannich reaction to prepare a reactive flame retardant LF, and then LF is further used as a reactant to condense with 4,4-MDI to generate a polyurethane foam LFPU. The demethylation of lignin not only enhances its Mannich reactivity with 2NH2DOPO, but also enhances the active sites of the condensation reaction with isocyanate. The flame retardant and thermal barrier properties of the polyurethane foam are improved. This green energy sustainable development manufacturing process, as well as the cost-effectiveness of the final product, can open up new ways to produce stable and strong bioplastics from abundant, renewable and sustainable biomass.
[0005] In order to achieve the above object, the technical solution of the present invention is as follows:
[0006] The present invention provides a method for preparing a polyurethane flame-retardant foam material of a phenolic hydroxyl-rich lignin derivative, comprising the following steps:
[0007] 1) adding alkali lignin to an acidic inorganic molten salt hydrate, stirring under heating conditions to react, adding ethanol aqueous solution after the reaction, precipitating lignin by an anti-solvent method, and then freeze-drying to obtain demethylated lignin;
[0008] 2) dissolving the demethylated lignin obtained in step 1) and 2NH2DOPO in N,N-dimethylformamide solution, and stirring to react;
[0009] 3) adding formaldehyde aqueous solution to the solution obtained in step 2), stirring, and performing a Mannich reaction, wherein the formaldehyde reacts with the carbon atom adjacent to the phenolic hydroxyl group of the lignin and the primary amine of 2NH2DOPO through the Mannich reaction;
[0010] 4) adding the solution obtained in step 3) into an ethanol aqueous solution, precipitating the precipitate by an anti-solvent method, and then freeze-drying to obtain a lignin flame retardant;
[0011] 5) dissolving the lignin flame retardant obtained in step 4) in PEG-400, adding dibutyltin dihydrate, water, silicone oil, Tween 80, and triethanolamine, and stirring under heating to react to obtain a reaction solution A;
[0012] 6) adding molten 4,4-MDI to the reaction solution A, stirring, and then pouring into a mold for foaming and ripening to obtain the polyurethane foam; in this process, the polyol and the isocyanate first undergo a condensation reaction, and then further utilizing the chemical structure characteristics of the polyol to cause cross-linking between molecular chains.
[0013] In the above technical solution, further, in step 1), the acidic inorganic molten salt hydrate is a mixed solution of LiBr aqueous solution and acid, wherein the concentration of LiBr aqueous solution is 60%, the concentration of acid is 0.2-1.0 mol / L, and the acid is hydrobromic acid;
[0014] The heating temperature is 60-140° C., and the reaction time is 30-150 min.
[0015] In the above technical solution, further, in step 2), the mass ratio of the demethylated lignin to 2NH2DOPO is 1:1.5.
[0016] In the above technical solution, further, in step 3), the mass ratio of the demethylated lignin to formaldehyde is 1:1.8;
[0017] The concentration of the formaldehyde aqueous solution is 30wt%;
[0018] The conditions of the Mannich reaction are: reaction temperature is 60-80°C and reaction time is 4-8 hours.
[0019] In the above technical solution, further, in step 5), the mass of the lignin flame retardant accounts for 15% of the total mass of the lignin flame retardant and PEG-400;
[0020] The mass of dibutyltin dihydrate, water, silicone oil, Tween 80 and triethanolamine are 0.4%, 0.2%, 0.8%, 0.7% and 0.4% of the mass of PEG-400 respectively;
[0021] The reaction temperature is 60-80°C.
[0022] In the above technical solution, further, in step 6), the mass ratio of the reaction solution A to 4,4-MDI is 1:1.5;
[0023] The stirring speed is 900-1200r / min;
[0024] The foaming time is 1-5min;
[0025] The aging temperature is 100-120°C.
[0026] The beneficial effects of the present invention are:
[0027] The present invention increases the phenolic hydroxyl content by demethylating lignin to obtain demethylated lignin with a high phenolic hydroxyl concentration, and then uses the Mannich reaction to react the primary amine group of 2NH2DOPO with the carbon atom of the adjacent position of the benzene ring of lignin, introduces the lignin molecular chain segment to obtain a reactive lignin flame retardant LF, and finally dissolves the lignin in PEG-400, and the two are used as polyurethane reactants to form a flame-retardant polyurethane material through condensation polymerization. The DOPO flame retardant group is introduced into the Mannich reaction process to enhance the flame retardant properties of the polyurethane foam, and the carbonization effect of lignin is improved on the basis of the acid source flame retardant effect. In addition, the amino group of the 2NH2DOPO chain segment causes the polyurethane material to be gas-phase flame-retardant and is further wrapped in the lignin combustion carbon layer, so as to have a good multi-element expansion flame retardant effect, and its limiting oxygen index value reaches 34.5% and reaches the UL94 flammability test V-0 level. In addition, the lignin phenylpropane structure in the polyurethane molecular chain enhances its mechanical properties and thermal barrier effect.
[0028] The polyurethane flame retardant foam material derived from lignin prepared by the present invention not only has flame retardant effect but also has excellent thermal barrier and mechanical properties. This green energy manufacturing process, as well as the cost-effectiveness of the final product, opens up a new way to produce stable and strong biomass materials from abundant, renewable and sustainable biomass. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is the infrared spectrum of the lignin flame retardant sample in Example 3;
[0030] Figure 2 is the nuclear magnetic resonance phosphorus spectrum of the demethylated lignin sample in Examples 1-6;
[0031] Figure 3 This is the nuclear magnetic resonance hydrogen spectrum of the lignin flame retardant sample of Example 3;
[0032] Figure 4 The XPS element analysis diagram of the lignin flame retardant samples of Examples 1-6;
[0033] Figure 5 The thermal weight loss curves of different polyurethane foam samples of Example 3, Comparative Example 1 and Comparative Example 2;
[0034] Figure 6 The thermal weight loss rates of different polyurethane foam samples of Example 3, Comparative Example 1 and Comparative Example 2;
[0035] Figure 7 This is a water contact angle diagram of the polyurethane foam sample of Example 3;
[0036] Figure 8 Infrared thermal imaging analysis of the polyurethane foam sample of Example 3;
[0037] Fig. 9 The stress-strain curves of different polyurethane foam samples of Examples 1-6 and Comparative Example 1;
[0038] Fig.10 The limiting oxygen index values of different polyurethane foam samples in Examples 1-6 and Comparative Example 1;
[0039] Fig.11 The Raman spectrum of the combustion carbon residue of the polyurethane foam sample of Example 3;
[0040] Fig.12 This is the SEM image of the carbon layer on the combustion surface of the polyurethane foam sample of Example 3. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0042] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0043] The present invention provides a method for preparing a polyurethane flame-retardant foam material of a phenolic hydroxyl-rich lignin derivative, comprising the following steps:
[0044] 1) adding alkali lignin to an acidic inorganic molten salt hydrate, stirring under heating conditions to react, adding ethanol aqueous solution after the reaction, precipitating lignin by an anti-solvent method, and then freeze-drying to obtain demethylated lignin;
[0045] 2) dissolving the demethylated lignin obtained in step 1) and 2NH2DOPO in N,N-dimethylformamide solution, and stirring to react;
[0046] 3) adding formaldehyde aqueous solution to the solution obtained in step 2), stirring, and performing Mannich reaction;
[0047] 4) adding the solution obtained in step 3) into an ethanol aqueous solution, precipitating the precipitate by an anti-solvent method, and then freeze-drying to obtain a lignin flame retardant;
[0048] 5) dissolving the lignin flame retardant obtained in step 4) in PEG-400, adding dibutyltin dihydrate, water, silicone oil, Tween 80, and triethanolamine, and stirring under heating to react to obtain a reaction solution A;
[0049] 6) Adding molten 4,4-MDI into the reaction solution A, stirring, and then pouring into a mold for foaming and aging to obtain a phenolic hydroxyl-rich lignin derivative polyurethane foam.
[0050] In step 1), the acidic inorganic molten salt hydrate is a mixed solution of LiBr aqueous solution and hydrobromic acid, wherein the concentration of LiBr aqueous solution is 60%, and the concentration of hydrobromic acid is 0.2-1.0 mol / L; the heating temperature is 60-140° C., and the reaction time is 30-150 min.
[0051] In step 2), the mass ratio of demethylated lignin to 2NH2DOPO is 1:1.5.
[0052] In step 3), the mass ratio of demethylated lignin to formaldehyde is 1:1.8; the concentration of the formaldehyde aqueous solution is 30 wt%; and the conditions of the Mannich reaction are: the reaction temperature is 60-80° C. and the reaction time is 4-8 hours.
[0053] In step 5), the mass of the lignin flame retardant accounts for 15% of the total mass of the lignin flame retardant and PEG-400; the masses of dibutyltin dicarboxylate, water, silicone oil, Tween 80, and triethanolamine are 0.4%, 0.2%, 0.8%, 0.7%, and 0.4% of the mass of PEG-400, respectively; and the reaction temperature is 60-80°C.
[0054] In step 6), the mass ratio of reaction liquid A to 4,4-MDI is 1:1.5; the stirring speed is 900-1200 r / min; the foaming time is 1-5 min; and the aging temperature is 100-120°C.
[0055] The demethylated lignin Lig and 2NH2DOPO flame retardant compounds are reacted by Mannich reaction to prepare reactive lignin flame retardant LF containing phosphorus and nitrogen elements, and LF and 4,4-MDI are polycondensed to prepare polyurethane foam rich in phenolic hydroxyl lignin derivatives.
[0056] The polyurethane flame-retardant foam material rich in phenolic hydroxyl lignin derivative prepared by the invention can be applied to flame-retardant and heat-insulating building materials.
[0057] The polyurethane flame retardant foam material of the phenolic hydroxyl-rich lignin derivative prepared by the present invention has a limiting oxygen index value of 34.5% and reaches the V-0 level. In addition, due to its special chemical structure, it has a barrier property of 0.012W / mK and a hydrophobic effect of 115.5°. By modifying the chemical structure of lignin, its flame retardant application in polymer materials is enhanced, opening up a new way for the high-value utilization of lignin.
[0058] Example 1
[0059] A method for preparing a polyurethane flame-retardant foam material rich in phenolic hydroxyl lignin derivatives comprises the following steps:
[0060] 1) 4 g of alkali lignin was added to 40 mL of acidic inorganic molten salt hydrate (a mixed solution of 60% LiBr aqueous solution and 0.6 mol / L HBr), and the mixture was stirred and reacted at 80° C. for 150 min. After the reaction, 250 mL of ethanol / water = 2 / 8 (v / v) was used to obtain lignin particles by an anti-solvent method, and then freeze-dried to obtain demethylated lignin, which was recorded as Lig2;
[0061] 2) dissolving 4 g of Lig2 obtained in step 1) and 6 g of 2NH2DOPO in 100 mL of N,N-dimethylformamide solution, and stirring to react;
[0062] 3) adding 24 g of 30 wt% formaldehyde aqueous solution to the solution obtained in step 2), stirring and reacting at 80° C. for 4 h to perform a Mannich reaction;
[0063] 4) pouring the solution obtained in step 3) into 250 mL of ethanol / water = 2 / 8 (v / v) solution, precipitating by anti-solvent method and freeze-drying to obtain lignin flame retardant, recorded as LF2;
[0064] 5) 1.5 g of lignin flame retardant LF was dissolved in 8.5 g of polyethylene glycol (PEG-400), and 0.04 g, 0.02 g, 0.08 g, 0.07 g and 0.04 g of dibutyltin dihydrate, water, silicone oil, Tween 80 and triethanolamine were added respectively, and stirred for reaction at 80° C. to obtain reaction solution A;
[0065] 6) 15 g of 4,4-MDI was heated at 60° C. until it melted, and the melted 4,4-MDI was added to 10 g of reaction solution A, and the mixture was rapidly stirred at a speed of 1000 rpm / min. The mixture was poured into a mold and foamed for 1 minute, and then aged at 120° C. to obtain a polyurethane foam, which was recorded as LF2PU.
[0066] Example 2
[0067] The preparation method of polyurethane foam is similar to that of Example 1, except that in step 1), the reaction is stirred for 30 min at 140° C. The demethylated lignin obtained in Example 2 is denoted as Lig5, the obtained lignin flame retardant LF5, and the obtained polyurethane foam is denoted as LF5PU.
[0068] Example 3
[0069] The preparation method of polyurethane foam is similar to that of Example 1, except that in step 1), the reaction is stirred for 110 min at 90° C. The demethylated lignin obtained in Example 3 is denoted as Lig11, the obtained lignin flame retardant LF11, and the obtained polyurethane foam is denoted as LF11PU.
[0070] Example 4
[0071] The preparation method of the polyurethane foam is similar to that of Example 1, except that in step 1), the acidic inorganic molten salt hydrate is a mixed solution of 60% LiBr aqueous solution and 0.2 mol / L HBr, and the reaction is stirred at 80° C. for 90 min. The demethylated lignin obtained in Example 4 is denoted as Lig13, the obtained lignin flame retardant LF13, and the obtained polyurethane foam is denoted as LF13PU.
[0072] Example 5
[0073] The preparation method of polyurethane foam is similar to that of Example 1, except that in step 1), the reaction is stirred for 30 min at 80° C. The demethylated lignin obtained in Example 5 is denoted as Lig14, the obtained lignin flame retardant LF14, and the obtained polyurethane foam is denoted as LF14PU.
[0074] Example 6
[0075] The preparation method of the polyurethane foam is similar to that of Example 1, except that in step 1), the acidic inorganic molten salt hydrate (60% LiBr aqueous solution / 0.2 mol / L HBr) is stirred for reaction at 110° C. for 30 min. The demethylated lignin obtained in Example 6 is denoted as Lig15, the obtained lignin flame retardant LF15, and the obtained polyurethane foam is denoted as LF15PU.
[0076] Comparative Example 1
[0077] (1) adding 0.04 g, 0.02 g, 0.08 g, 0.07 g and 0.04 g of dibutyltin dihydrate, water, silicone oil, Tween 80 and triethanolamine to 10 g of polyethylene glycol (PEG-400) respectively, stirring and reacting at 80° C. to obtain a reaction solution;
[0078] (2) 15 g of 4,4-MDI was heated at 60° C. until it melted, and the melted 4,4-MDI was added to 10 g of the reaction solution, which was rapidly stirred at a speed of 1000 rpm / min. The mixture was poured into a mold and foamed for 1 min, and then aged at 120° C. to obtain a polyurethane foam, which was recorded as PU.
[0079] Comparative Example 2
[0080] Using chemically unmodified alkali lignin, the method comprises the following steps:
[0081] 1) 1.5 g of alkali lignin AL was dissolved in 8.5 g of polyethylene glycol (PEG-400), and 0.04 g, 0.02 g, 0.08 g, 0.07 g and 0.04 g of dibutyltin dihydrate, water, silicone oil, Tween 80 and triethanolamine were added respectively, and stirred for reaction at 80° C. to obtain a reaction solution A;
[0082] 2) 15 g of 4,4-MDI was heated at 60° C. until it melted, and the melted 4,4-MDI was added to 10 g of reaction solution A, and the mixture was rapidly stirred at a speed of 1000 rpm / min. The mixture was poured into a mold and foamed for 1 minute, and then aged at 120° C. to obtain a polyurethane foam, which was recorded as ALPU.
[0083] Figure 1 is the infrared spectrum of the lignin flame retardant sample in Example 3, from Figure 1 It can be seen that 2NH2DOPO is comparable to DOPO at 3405cm -1 and 2912cm -1 The -NH2- and -CH2- stretching peaks appear at the positions, and 2NH2DOPO still contains 1240 cm -1 (P-Ph) and 912cm -1 Compared with other samples, LF has a peak at 3500-3000cm-1 The stretching peak in the range is reduced and becomes a sharp peak. -1 (P-Ph) and 912cm -1 (P=O) position, containing the characteristic peak of chemical bond of phosphaphenanthrene structure with DOPO structure. This indicates that in the process of synthesizing lignin flame retardant, lignin phenolic hydroxyl group participates in Mannich reaction to generate compounds with amino and phosphaphenanthrene characteristics. And in the reaction process, lignin flame retardant LF has a higher peak at 1600cm-1 than other samples. -1 -400cm -1 The range includes both lignin benzene ring (1650cm -1 ) and -CH2- structure (2900cm -1 ) characteristic peaks, including 1240cm -1 (P-Ph) and 912cm -1 (P=O) characteristic peak of phosphaphenanthrene. Figure 2 As shown in Table 1, the demethylated lignin Lig 31 The results of PNMR studies show that the phenolic hydroxyl content of the demethylated lignin prepared in different embodiments increases, and the phenolic hydroxyl concentration of Lig11 prepared in Example 3 is 7.40 mmol / L.
[0084] Table 1 Demethylated lignin 31 PNMR score results
[0085] Functional group type Lig2 Lig5 Lig11 Lig13 Lig14 Lig15 Aliphatic-OH 0.43 0.89 0.82 0.56 0.62 0.56 S-OH 0.07 0.04 0.17 0.12 0.03 0.03 G-OH 5.17 3.32 7.38 6.28 0.78 1.58 H-OH 0.01 0.01 0.01 0.01 0.01 0.01 COOH 0.28 0.21 0.47 0.32 0.14 0.14 Total Ph-OH 5.25 3.37 7.40 6.42 0.82 1.62 Total OH 12.99 5.96 8.85 6.97 1.58 2.32
[0086] Figure 3 is the lignin flame retardant sample in Example 3 1 In HNMR, the characteristic peaks of lignin benzene ring and aliphatic peaks appeared, and the chemical shift of phosphaphenanthrene structure was enhanced. It can be found that the LF peak shifted at 6.94-8.0ppm and the main peak shift of 2NH2DOPO to amino hydrogen appeared at 5.06ppm and 2.49ppm.
[0087] Figure 4 The XPS elemental analysis results of lignin flame retardant LF with different phenolic hydroxyl contents showed that LF had characteristic peaks of N1s and P2p compared with alkali lignin. This further indicated that the 2NH2DOPO flame retardant chain segment was introduced into the hydroxyl-rich lignin oligomer molecular chain through the Mannich reaction.
[0088] like Figure 5 and Figure 6 As shown in the thermogravimetric analysis of LFPU, as the temperature rises, comparative example 1 begins to degrade, and then comparative example 2 and example 3 also begin to degrade. Compared with comparative example 1, when a certain proportion of lignin components is added, T 5%(301.38℃, 294.43℃) and T 10% (309.98°C, 314.42°C) were all increased. 5% is lower than that of Comparative Example 2, but as the temperature increases, the T 10% The thermal weight loss rate peak value of Example 3 is significantly lower than that of Comparative Example 2 and Comparative Example 1. Since the composite material of Example 2 contains some aminomethyl structures generated by the Mannich reaction, bond breakage and thermal degradation occur at around 300°C. The TG curve shows that lignin substantially improves the thermal stability of the composite material, and the PO-Ph and P=O in the lignin flame retardant with an organic phosphorus phenanthrene structure and the lignin benzene ring jointly improve the thermal stability of the composite material. The T of Example 3 10% and T max All are greater than Comparative Example 2 and Comparative Example 1. The residual carbon rates of Comparative Example 1, Comparative Example 2 and Example 3 are 10.85%, 11.68% and 15.93%, respectively. During the thermal decomposition process, the organic phosphorus structure flame retardant promotes the re-carbonization ability of lignin during decomposition, resulting in a certain high carbonization rate of the flame-retardant polyurethane foam with a phosphaphenanthrene structure. Therefore, the introduction of nitrogen and phosphorus element flame retardants through the Mannich reaction significantly improves the thermal stability of the composite material, and exerts the high carbonization of the lignin-based composite material after thermal decomposition.
[0089] Table 2 T of polyurethane foam samples of Example 3, Comparative Example 1 and Comparative Example 2 5% , T 10% , T max and carbon residue rate
[0090] Example Sample <![CDATA[T 5% (℃)]]> <![CDATA[T 10% (℃)]]> <![CDATA[T max (℃)]]> Carbon residue rate (%) Comparative Example 1 262.61 284.07 337.36 10.85 Comparative Example 2 301.83 309.98 344.37 11.68 Example 3 294.43 314.42 346.25 15.93
[0091] Figure 7 It can be observed that lignin flame retardant acts as a soft chain in the polyurethane polymer chain segment. Since lignin has hydrophobic chemical groups after chemical modification, the composite foam has a 115.5° hydrophobic structure through hydrophilic-hydrophobic testing. Figure 8 As shown, in addition, the composite foam was scanned and monitored by infrared imaging technology, and the xenon lamp provided heat on the surface of the composite material in Example 3. After 10 minutes of illumination, it was found that the internal temperature of the composite material changed gradually from 30°C to 17°C. This is attributed to the fact that not only the dense pore structure inside the composite material reduces the thermal conductivity, but also the conjugated chemical bonds of the main phenylpropane compounds of the lignin component have anti-thermal conductivity to the ultraviolet light part of the xenon lamp, reflecting the heat from the xenon lamp to block the heat flow.
[0092] As shown in Table 3, the thermal conductivity of the polyurethane foam samples was tested and it was found that the lignin-based flame-retardant polyurethane foam prepared from phenolic hydroxyl-rich lignin derivatives had a lower thermal conductivity and better thermal barrier properties.
[0093] Table 3 Thermal conductivity of polyurethane foams of Examples 1-6 and Comparative Examples 1-2
[0094] Example Sample Thermal conductivity (W / m·K) Comparative Example 1 0.0384 Comparative Example 2 0.0312 Example 1 0.0286 Example 2 0.0275 Example 3 0.0212 Example 4 0.0225 Example 5 0.0295 Example 6 0.0275
[0095] like Fig. 9 As shown, all example samples were subjected to stress-strain tests, and the results showed that Example 3 had better compressive mechanical properties than other example samples, and the higher the phenolic hydroxyl concentration, the stronger the compressive properties of the prepared LFPU.
[0096] The combustion behavior of LFPU polyurethane foam was evaluated using the limiting oxygen index (LOI) and horizontal and vertical combustion tests. Fig.10 As shown. During the combustion process, the comparative example 1 has a fast burning speed and is accompanied by black smoke and dripping. The LOI of pure PU is relatively low (20.7%), and the LOI of the comparative example 2 composite material with the addition of pure lignin is only increased by 22.5, but black smoke and dripping still exist during the combustion process, and the vertical and horizontal combustion levels reach V-2. In addition, during the combustion process, it was found that the phenolic hydroxyl content of the depolymerized lignin prepared under different process conditions was different, and the combustion phenomena of the prepared lignin flame retardant composite materials were also different. The phenolic hydroxyl concentration of Example 5 is 0.98 mmol / L, and the burning time of Example 5 is slow. The LOI value of Example 5 is 22.9%, and the vertical and horizontal combustion levels reach the V-2 level.
[0097] Among all polyurethane foams, Example 3 has good flame retardant properties. The composite material of Example 3 burns slowly during the combustion process, and begins to produce a self-extinguishing effect after burning for 5 seconds, without black smoke and dripping. During the combustion process, accompanying gases are generated on the surface of the substrate, but after extinguishing, a dense residual carbon structure is generated on the surface of the substrate. The oxygen index value of Example 3 is 34.5%, reaching the V-0 combustion grade. Through the combustion behavior of the composite material, it can be concluded that lignin can improve the thermal stability of polyurethane materials. The flame retardant properties of polyurethane foams prepared by aminated lignin flame retardants are different due to different lignin phenolic hydroxyl content. The higher the phenolic hydroxyl concentration of demethylated lignin, the more flame retardant the 2NH2DOPO flame retardant group is introduced through the Mannich reaction. During the combustion process, NH and OP=O condense with the lignin breakage group to form carbon to improve the carbonization of the composite material. As a result, the chemical structure of the depolymerized lignin changes, realizing its high-value utilization in flame-retardant polymer materials.
[0098] Table 4 Flame retardant performance indexes of polyurethane foams of Examples 1-6 and Comparative Examples 1-2
[0099]
[0100] like Fig.11As shown, the combustion residues of Comparative Example 1, Comparative Example 2 and Example 3 were subjected to Raman spectroscopy analysis. ID / IG represents the sp2 graphitization degree of the carbon layer. The smaller the ratio, the higher the graphitization degree of the carbon layer. The ID / IG ratios of Comparative Example 1, Comparative Example 2 and Example 3 are 0.72, 0.63 and 0.48 respectively. Lignin flame retardant LF is used as a reactant to enhance the density of the carbon layer. Thereby improving the protective layer of the combustion surface and further retardant the spread of the combustion.
[0101] Fig.12 This is a SEM image of the surface of the carbon layer after combustion in Example 3. The burned carbon layer is dense and flat, and there are certain bubbles and protrusions. LF flame retardant is an intumescent flame retardant that exerts a multi-element synergistic effect and enhances the flame retardant effect of lignin flame retardant polyurethane foam.
[0102] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.
Claims
1. A method for preparing a polyurethane flame retardant foam material rich in phenolic hydroxyl lignin derivatives, characterized in that: The following steps are involved: 1) adding alkali lignin to an acidic inorganic molten salt hydrate, stirring under heating conditions to react, adding ethanol aqueous solution after the reaction, precipitating lignin by an anti-solvent method, and then freeze-drying to obtain demethylated lignin; 2) dissolving the demethylated lignin obtained in step 1) and 2NH2DOPO in N,N-dimethylformamide solution, and stirring to react; 3) adding formaldehyde aqueous solution to the solution obtained in step 2), stirring, and performing a Mannich reaction; 4) adding the solution obtained in step 3) into an ethanol aqueous solution, precipitating the precipitate by an anti-solvent method, and then freeze-drying to obtain a lignin flame retardant; 5) dissolving the lignin flame retardant obtained in step 4) in PEG-400, adding dibutyltin dihydrate, water, silicone oil, Tween 80, and triethanolamine, and stirring under heating to react to obtain a reaction solution A; 6) adding molten 4,4-MDI into the reaction solution A, stirring, and then pouring into a mold for foaming and then ripening to obtain the polyurethane foam.
2. The preparation method according to claim 1, characterized in that: In step 1), the acidic inorganic molten salt hydrate is a mixed solution of LiBr aqueous solution and hydrobromic acid, wherein the concentration of the LiBr aqueous solution is 60% and the concentration of the hydrobromic acid is 0.2-1.0 mol / L; The heating temperature is 60-140° C., and the reaction time is 30-150 min.
3. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of the demethylated lignin to 2NH2DOPO is 1:1.
5.
4. The preparation method according to claim 1, characterized in that: In step 3), the mass ratio of the demethylated lignin to formaldehyde is 1:1.8; The concentration of the formaldehyde aqueous solution is 30wt%; The conditions of the Mannich reaction are: reaction temperature is 60-80°C and reaction time is 4-8 hours.
5. The preparation method according to claim 1, characterized in that: In step 5), the mass of the lignin flame retardant accounts for 15% of the total mass of the lignin flame retardant and PEG-400; The mass of dibutyltin dihydrate, water, silicone oil, Tween 80 and triethanolamine are 0.4%, 0.2%, 0.8%, 0.7% and 0.4% of the mass of PEG-400 respectively; The reaction temperature is 60-80°C.
6. The preparation method according to claim 1, characterized in that: In step 6), the mass ratio of the reaction solution A to 4,4-MDI is 1:1.5; The stirring speed is 900-1200r / min; The foaming time is 1-5min; The aging temperature is 100-120°C.
Citation Information
Patent Citations
Preparation and application methods of lignin-based flame retardant
CN107245138A
Modified lignin-based biomass gel and preparation method thereof
CN114920979A
Toughening type lignin flame retardant as well as preparation method and application thereof
CN115947953A